O olhar docente sobre escuta, autoria e protagonismo das crianças em uma escola municipal de educação infantil na cidade de São Paulo: conquistas e desafios - Alboz, Vivian (2016)
How the teachers can promote the communication with children in the educative space in child education? How this dialogues contributes to the constrution of new and meaningful learning? How teachers have the ability to planning considering children’s will? How teachers can promote children’s paternity, jumping them to the stage in their own education? Focusing on such concerns, this essay search for the understanding on how educators from “Ciranda” school listen the children and transform it in the educative practice, in order to assure the participation and paternity of the children. The case study was realized in a public school located in the city of São Paulo, taking advantage of a strong background in the theory, focused on the reviews of the masterminds in childhood sociology and specialists in childhood education, wich are contributing to a new concept of children as the agent, competent and producer of culture. Some publications from the Ministry of Education of Brasil and Secretary of education of São Paulo are complimentary for such essay. The methodology applied had a qualitative approach, including procedures of semi structure interviews with teachers and an analysis of the documents from the Political Pedagogic Project of the school. The essay unfold that the principles evidenced for the consolidation of a dialogue between children-adults at the same level and in partnership in this school are as follows: listening, think-tanks with daily methodology, appreciation of childhood production, pedagogical documentation, co-jointly planning and decisions taking with children and adults. It was also noted that in this context, educators were able to deconstruct practices coming from the banking model pedagogy and streamlining. This essay intends to contribute for the searching of new tracks to childhood education with researches unveiling infant voices, translating it into the favor of themselves, assuring the consolidation of their rights